2020
DOI: 10.3389/fgene.2020.00418
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Analysis of a ceRNA Network Reveals Potential Prognostic Markers in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide and is derived from an accumulation of genetic and epigenetic changes. This study explored potential prognostic markers in CRC via the construction and in-depth analysis of a competing endogenous RNA (ceRNA) network, which was generated through a three-step process. First, we screened candidate hub genes in CRC as the primary gene markers to survey their related regulatory non-coding RNAs, miRNAs. Second, the interacting mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 99 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…Here we investigated the availability of a shared ceRNA network of four common HD cancers. Previous HD cancerrelated ceRNA analyses have focused on lncRNA-associated networks [6][7][8][9][10]. We extended the scope of ceRNA research to include pseudogene-associated cross-HD cancer ceRNA networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we investigated the availability of a shared ceRNA network of four common HD cancers. Previous HD cancerrelated ceRNA analyses have focused on lncRNA-associated networks [6][7][8][9][10]. We extended the scope of ceRNA research to include pseudogene-associated cross-HD cancer ceRNA networks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous bioinformatics studies have identified ceRNA candidates as prognostic or predictive biomarkers for common cancer types such as colorectal, endometrial, prostate, and breast cancers [6][7][8][9][10]. Several web-based tools such as miRTissuece, LncACTdb 2.0, and lnCeDB have been developed, supporting the search for ceRNA interactions networks in multiple tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous bioinformatics studies have identified ceRNA candidates as prognostic or predictive biomarkers for common cancer types such as colorectal, endometrial, prostate, and breast cancers [6][7][8][9][10]. Several web-based tools such as miRTissue ce , LncACTdb 2.0, and lnCeDB have been developed, supporting the search for ceRNA interaction networks in multiple tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several web-based tools such as miRTissue ce , LncACTdb 2.0, and lnCeDB have been developed, supporting the search for ceRNA interaction networks in multiple tissues [11][12][13]. A recent colorectal cancer ceRNA study identified a network of nine hub genes, thirteen lncRNAs, and twenty-nine candidate miRNAs, integrating multiple genomic datasets [6]. The authors further revealed the MFAP5-miR-200b-3p-AC005154.6 axis as a potential biomarker of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%